Bunium incrassatum Bois. Batt. Trab. (Talghouda) in the improvement of thyroid tissue damages in female rats - Meriem Aiouaz; Arezki Bitam (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to determine the nutritional and therapeutic effects of dried Bunium incrassatum Bois.Batt.Trab. Tubers powder on rats with hyper and hypothyroidism. Thirty female Wistar rats were divided into 6 groups. G1 (C) received a normal diet. G2 (CT) received a normal diet with dried Talghouda tubers powder dissolved in water. G3 (Hpo) was treated with Carbimazole® (5 mg/day) for 6 weeks. G4 (HpoT) was treated with Carbimazole® (5 mg/day) for 6 weeks and Talghouda for 7 weeks after induced hypothyroidism. G5 (Hpy) was treated with Levothyroxine® (600µg/Kg body weight/day) for 6 weeks. G6 (HpyT) had hyperthyroidism induced by Levothyroxine® (600µg/Kg body weight/day) for 6 weeks and then treated with Talghouda for 7 weeks. A dose of Talghouda was chosen at 1.03g/Kg body weight/day, and all treatments were given by gavage. Phytochemical analysis was carried out for Talghouda, and the thyroid glands of each group were then recovered for histological study. Talghouda treatment showed a highly significant (p 0.01) increase in body weight in groups G2, G4 and G6 with gland repair and reactivation of thyroid follicles in hyper and hypothyroid rats compared to G1, G3 and G5. The powder of dried Talghouda tubers, used as traditional medicine in Algeria, improved the damages caused by hyper and hypothyroidism.